Polypeptides associated with in vitro cyst formation of Blastocystis hominis - Ithoi, Init; Mak, J.W.; Top, S.; Zulhainan, Z.; Prummongkol, S.; Nissapatorn, V.; Wan-Yusoff, W.S.; Anuar, A.K. (SEAMEO Regional Tropical Medicine and Public Health Network, 2003)
The objective of this study was to characterize the polypeptides associated with cysts of Blastocystis hominis. This form is believed to be infective and plays a role in parasite resistance to anti-B. hominis drugs currently used for treatment of Blastocystis associated diarrhea. Cysts were induced through in vitro culture of the parasite in complete medium supplemented with bacterial extract with trypticase, metronidazole or doxycycline. SDS-PAGE analysis showed almost similar polypeptide patterns of parasite extracts obtained from in vitro cultured parasites before and after exposure with the three supplements. Polypeptide bands at 76, 58.5, 48, 45, 40, 38, 32, 25 and 22 kDa were constantly seen in all antigenic preparations and no specific cyst-associated polypeptide was present. However, on immunoblot analysis, 3 out of 16 blastocystosis human sera identified a cyst-associated polypeptide at 60 kDa in all parasite extracts prepared from cultures with the three supplements. In addition, there were associated morphological changes detected in these parasites stained with acridine orange and observed under fluorescence microscopy. Metronidazole induced cyst forms (reddish cells) as early as 12 hours post-exposure; more cyst production (with stronger immunoblot bands) occurred after 24 hours exposure. However, cysts rupture with release and destruction of B. hominis daughters cells occurred after 48 hours exposure. Doxycycline induced less cyst-like forms at 24 hours (weaker 60 kDa band) and less destruction of the cysts (60 kDa band still present at 72 hours post exposure). Bacterial extract and trypticase also induced cysts at 12 hours with increasing numbers up to 72 hours exposure (corresponding increase in intensity of 60 kDa band from samples harvested at 12 to 72 hours post exposure) without any sign of deleterious effect on the parasite.